Profile of Critical Thinking Skills Test Assisted by E-Instrument as an Innovation of Conventional Student Tests to Improving Quality Education - Lintangesukmanjaya, Rahmatta Thoriq; Prahani, Binar Kurnia; Dwikoranto, Dwikoranto; Jatmiko, Budi; Utami, Arfiati Ulfa; Moniz, Joana Paula Gerabella da Costa; Bergsma, Lindsay N. (International Journal of Current Educational Research, 2025)
Objective: The study aims to determine the profile of students' critical thinking skills using E-Instruments. In this study, the profile of students' critical thinking skills, as assessed with conventional tests and E-instruments, is also compared. Method: The analysis of critical thinking skills profiles was conducted using quantitative methods. The study was conducted at a high school in East Java, Indonesia, that had used the independent curriculum. The population of this study was sampled purposively, comprising 65 students. Results: The profile of students' critical thinking skills in physics material is still relatively low. Based on the Wilcoxon test, the findings indicate that there is no significant difference between the test results obtained from conventional tests and those from E-instruments. Novelty: The novelty of this research lies in the application of E-instruments as a substitute for conventional instruments in measuring students' critical thinking skills. Its manifestation is in the implementation of point 4 of the SDGs, which aims to improve the quality of education in the field of digital technology. On the other hand, the level of students' critical thinking skills is determined by the difficulty of the material and the skill indicators that are drilled. In the future, comprehensive learning devices and models can be developed as alternatives to enhance students' skills, particularly in the use of digital technology, including media, devices, and assessment instruments, thereby increasing students' enthusiasm for learning.